Strengthening State Plans for Human Development: District Level Vital Statistics - Planning Commission (Planning Commission, 2008)
In India, the State Human Development Reports (SHDRs) over time have generated greater recognition and demand for various commission or expert committee reports at local administration units like district for planning purposes under human development framework. Measurement of human development focuses on health, education and access to resources needed for a decent standard of living.
Planning Commission, United Nations Development Programme